Thromboembolic complications in cancer - Stanisławiak, Joanna; Markowska, Janina (Contemporary Oncology/Współczesna Onkologia, 2008)
Thrombosis is a frequent complication of cancer. The many signs and symptoms of the prothrombotic state in cancer range from asymptomatic basic abnormal coagulation tests to massive clinical thromboembolism, when the patient may be gravely ill. Deep venous thrombosis (DVT) of the leg and pulmonary embolism are the most common clinical manifestations of thromboembolic disease in cancer patients. Procoagulants such as tissue factor (TF) are expressed by many tumours, although platelet turnover and activity are also increased. Damaged endothelium and blood flow abnormalities may also play a part in cancer. The mechanisms of tumour-associated hypercoagulability may help to identify more targeted strategies to prevent thromboembolic complications in cancer patients, in particular when surgical or chemical therapy is involved.